Synthesis of new 1,3-dioxepin derivatives - (:unkn) unknown (COMITE VAN BEHEER VAN HET BULLETIN VZW, 1995)
Using cisa-buten-1,4-diol and mono and dicarbonyl compounds eleven new 4,7-dihydro-1,3-dioxepin derivatives were synthesized. Structures were proved by spectroscopic methods.